Action of dithiocarbimates salts on the honey bee and its pathogen Nosema ceranae - André Henrique de Oliveira; Mayura Marques Magalhães Rubinger; Anderson da Silva Rabello; Nathália Matias Albuini-Oliveira; Antonio Eustáquio Carneiro Vidigal; Marcelo Ribeiro Leite de Oliveira; Eder do Couto Tavares; José Eduardo Serrão (AMB Express, 2024)
Abstract Apis mellifera, crucial pollinators for both native and cultivated plants, also yield various products such as honey, wax, royal jelly, and propolis, extensively utilized in the food, pharmaceuticals, and cosmetics industries. Nosema ceranae, a prevalent microsporidian worldwide, stands as a significant pathogen for A. mellifera, showing resistance to conventional antibiotics. Consequently, the exploration of novel compounds for N. ceranae control becomes imperative. Dithiocarbimate derivatives emerge as promising antifungal candidates under evaluation for combating various pathogens, particularly those affecting plants. This study assessed the toxicity profile of six dithiocarbimate derivatives on A. mellifera worker survival and N. ceranae pathogen. Among these, four compounds exhibited minimal bee mortality and proceeded to further evaluation against N. ceranae. In vitro assays demonstrated their inhibitory effects on spore germination. Remarkably, the most potent compound suppressed N. ceranae spores by 62% at a concentration of 20 µmol L−1 in vivo. Thus, these dithiocarbimate derivatives represent promising new antifungal agents for combatting nosemosis in honey bee populations.